2012
DOI: 10.1080/09593330.2012.696719
|View full text |Cite
|
Sign up to set email alerts
|

Location and chemical composition of microbially induced phosphorus precipitates in anaerobic and aerobic granular sludge

Abstract: This work focuses on combined scanning electron microscopy and energy dispersive X-ray analysis (SEM-EDX) applied to granular sludge used for biological treatment of high-strength wastewater effluents. Mineral precipitation is shown to occur in the core of microbial granules under different operating conditions. Three dairy wastewater effluents, from three different upflow anaerobic sludge blanket (UASB) reactors and two aerobic granular sequenced batch reactors (GSBR) were evaluated. The relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Mañas et al (2012) also observed internal precipitation of calcium phosphate in anaerobic granules. 42 It was proposed that the increase in internal pH is because of biological consumption of H + during methanogenesis in anaerobic granules and contributed to the internal precipitation. 42 Therefore, the favorable internal conditions for Ca x (PO 4 ) y formation are most likely biologically induced.…”
Section: Resultsmentioning
confidence: 99%
“…Mañas et al (2012) also observed internal precipitation of calcium phosphate in anaerobic granules. 42 It was proposed that the increase in internal pH is because of biological consumption of H + during methanogenesis in anaerobic granules and contributed to the internal precipitation. 42 Therefore, the favorable internal conditions for Ca x (PO 4 ) y formation are most likely biologically induced.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the above, it can be concluded that the removal of phosphorus compounds could have occurred by precipitation of phosphorus as inorganic phosphate such as Ca 3 (PO 4 ) 2 and MgHPO 4 . Such a mechanism for phosphorus removal in AGS technology has been indicated by, among others, Filali et al [ 49 ] and Manas et al [ 50 ]. There was a high negative correlation between the TP removal and TP loading rate of biomass in the reactors supported by powdered materials.…”
Section: Resultsmentioning
confidence: 93%
“…a deficiency or excess of some macro (N, P, S) or micronutrients (Fe, Ni, Co, Mo, Ca, Al, Na, K, Se, W) that affect sludge growth, granule stability, or may cause their mineralization -i.e. replacement of active biomass by inorganic precipitates - (Guiot et al 1988;Grotenhuis et al 1991;Alphenaar et al 1993;El Mamouni et al 1995;Kim et al 2004;Jeison et al 2008;Speece 2008;Zandvoort et al 2006, Mañas et al 2012).…”
Section: Introductionmentioning
confidence: 99%